Cryptococcus spp. isolation from excreta of pigeons (Columba livia) in and around Monterrey, Mexico - Canónico González, Yolanda; Adame Rodríguez, Juan Manuel; Mercado Hernández, Roberto; Aréchiga Carvajal, Elva Teresa (2013)
The presence of Cryptococcus spp. has been reported in Mexico’s capital city; however, to our knowledge there are no reports of its presence in the state of Nuevo León located in northeast Mexico. This is presumed to be because the hot and dry climate in this region does not favor cryptococcal proliferation. This study confirmed the presence of C. neoformans and C. albidus in 20% (10/50) of randomly selected fecal samples of pigeons (Columba livia) in the Monterrey metropolitan area. The presence of this yeast in the state of Nuevo León is proof of its adaptation to the typically hot climate of the area and is consistent with recent reviews of cryptococcosis cases in several local hospitals. The two species were identified and characterized through microbiological tests and molecular identification by DNA extraction and PCR amplification of highly conserved 18S ribosomal DNA using ITS1 and ITS2 as target regions. The PCR products were sequenced and compared with those reported in GenBank.